Monetization Models in Video Games - Elshabrawy, Mustafa Tharwat Abdelsalam (2025)
The present research aimed to highlight the various monetisation models and the role of monetisation models, required age of games, price, and platforms in influencing (causing an increase/decrease) the players` achievements, positive ratings, negative ratings, average playtime nad median playtime of games. This thesis is based on the cross-sectional and quantitative research in which the dataset was collected from Kaggle. The data analysis included the frequency distribution, descriptive statistics of variables and then the normality of data were checked by using skewness and Kurtosis. After it was revealed that the data were not normally distributed then the non-parametric tests were conducted to achieve the asserted research objectives. Kruskal-Wallis test and Spearman`s tests were used to achieve the second research objective. The results of the Kruskal-Wallis test indicated that there was a significant difference in the players' achievements, positive ratings, negative ratings, average playtime, median playtime, and game prices across the various monetisation models. In addition, the results also revealed a significant difference in the players' achievements, positive ratings, negative ratings, average playtime, median playtime, and game prices across the required age of players and the various gaming platforms. Moreover, the results of Spearman`s test indicated that the price of games was positively and significantly associated with the players` achievements, positive ratings on the games, negative ratings, average playtime of players and median playtime of players.